Strategi Peningkatan Kemandirian Anak Usia Dini di TK. Dharma Wanita Brumbung 1 Kediri - Puspitasari, Dina Mei; Sa'diyah, Elok Halimatus (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2014)
The development of one's independence toward perfection becomes very important to be pursued since the early, more serious, systematic and programmed. As has been trying to do by the teacher in kindergarten. Dharma Wanita Brumbung I in order to increase the independence of children. Researchers interested in conducting research on the theme